Fiqh rulings and shari’ah objectives of Quranic competitions - bouaouira, soufian; allali, A mohamed (Journal of Social Sciences and Humanities, 2024)
The subject of Qur’anic competitions and the prizes that follow them is one of the new issues, as its forms have become saturated and multiplied and have become widespread in an unprecedented manner. This research aims to introduce the Qur’anic competitions and their legitimacy and explain their Fiqh rulings and Shari'ah objectives. The researcher used the existing descriptive analytical method. He relied on induction and deduction, and reached a number of results and recommendations, the most important of which is that Qur’anic competitions are legitimate according to the Qur’an, Sunnah, and consensus, and are allowed with compensation. The jurists have agreed on the permissibility of offering compensation from non-contestants or from one of them, but they disagreed about offering compensation from all of them with the presence of an analyst. The most likely opinion is that it is permissible and it is the doctrine of the majority, and it is forbidden without an analyst. One of the controls for Quranic competitions is that the objectives, means and scope of the competition must be legitimate, and it must not result in neglecting a duty or doing a forbidden act. The objectives of Quranic competitions lie in preserving religion, reason and money, and one of the most important recommendations is activating all types of Quranic competitions in memorization, recitation, readings, interpretation, contemplation, etc., and calling for increased interest among researchers in the subject of Qur’anic competitions, rooted